Herramientas discursivas y comunicacionales del discurso político. El caso de las campañas electorales españolas - Varchetta, Jacopo (Acta Hispanica, 2016)
The existing literature on political parties describes election campaigns as the mechanism by which candidates and parties compete in order to reach and obtain political power. Such campaigns are characterized by a series of formal, organizational and communicative activities, they represents indeed candidates and party leader’s effort in order to obtain as many votes as possible. Today campaigns represent a new type of political marketing, a set of technical research, planning, management and communication used in a set of strategic actions. The article aims to analyze the main discursive and communicative tools used in Spanish political campaigns propaganda, emphasizing those strategies related with media and storytelling.